Mass spectrometry as a powerful analytical tool for the characterization of indoor airborne microplastics and nanoplastics. Issue 4 (19th March 2021) - Velimirovic, Milica; Tirez, Kristof; Verstraelen, Sandra; Frijns, Evelien; Remy, Sylvie; Koppen, Gudrun; Rotander, Anna; Bolea-Fernandez, Eduardo; Vanhaecke, Frank
Abstract : In this review we discuss the novel developments in mass spectrometry-based analytical methods for size determination, chemical identification, and quantification of the microplastic and nanoplastic in indoor air and dust. Abstract : Development of analytical methods for the characterization (particle size determination, chemical identification, and quantification) of the low μm-range microplastics (MPs; 1–10 μm) and nanoplastics (NPs; 1 nm to 1 μm) in air – coarse (PM10 ; <10 μm), fine (PM2.5 ; <2.5 μm) and ultrafine (PM1 ; <1 μm) particulate matter – is a quickly emerging scientific field as inhalation has been identified as one of the main routes of human exposure. The respiratory tract may serve as both target tissue and port of entry to the systemic circulation for the inhaled MPs and NPs with their small particle size. As an outcome, the interest of the scientific community, policy makers, and the general public in indoor airborne MPs and NPs increased tremendously. However, there is a lack of detailed knowledge on the indoor and outdoor sources of MPs and NPs, their levels, and their health impact. This is mainly related to a lack of standardized sampling and analytical methods for size determination, chemical identification, and quantification. In this review, recent developments in mass spectrometry-based analytical methods for size determination, chemical identification, and quantification of the MPs and NPs in indoor air and dust, are discussed.